The DNA of strategy execution next generation project management and PMO - Duggal, Jack (John Wiley & Sons, 2018)
A transformative framework to bring the PMO into the future The DNA of Strategy Execution provides clear guidance and a practical framework for moving forward amidst the dynamic changes in todays business environment. The PMO walks a tightrope between creativity and structure, between innovation and bureaucracy; demands for formal structures and discipline counter the need to be responsive and adaptive